Science for Reducing Health Inequalities Emerges From Social Justice Movements. (May 2016) - Wing, Steve
Although the health sciences have investigated economic and social inequalities in morbidity and mortality for hundreds of years, health inequalities persist and are, by some measures, increasing. This is not simply a situation in which the knowledge exists but is not implemented. Rather, science in general and epidemiology in particular have focused on quantifying the effects of specific agents considered in isolation. This approach is powerful, but, in the absence of ecological concepts that connect parts and wholes, contributes to maintaining health inequalities. By joining movements for human rights and social justice, health scientists can identify research questions that are relevant to public health, develop methods that are appropriate to answering those questions, and contribute to efforts to reduce health inequalities.